When verbs ‘stay (and) go’ together: Pseudo-coordination in Juǀ’hoan and ǃXun - Pratchett, Lee J. (Stellenbosch Papers in Linguistics Plus, 2022)
Multi-verb constructions are an areal feature of Kalahari Basin Area languages (“Khoisan”), a Sprachbund comprising the Kx’a, Tuu, and Khoe-Kwadi families. Presently, these languages are characterised by two distinct multi-verb constructions with specific distributions: strictly contiguous serial verb constructions in Kx’a and Tuu correspond to multi-verb constructions involving a morphophonological linker, or “juncture”, in Khoe-Kwadi. This paper describes an additional multi-verb construction, namely pseudo-coordination. Drawing on a corpus of spontaneous discourse data, this paper demonstrates the rise of pseudo-coordination from a biclausal construction in Juǀ’hoan and ǃXun (Ju, Kx’a). The comparative analysis highlights the verbs that typically arise the context of pseudo-coordination and the resulting functions. This paper describes the polygrammaticalisation resulting from pseudo-coordination, including other multi-verb constructions.